Suprasegmental Phoneme Learning in Deaf Students in TK B Class (Descriptive study at SLB B Pangudi Luhur DKI Jakarta) - Elsyifa Irma Suryani; Suparno Suparno (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This study seeks information about Suprasegmental Phoneme Learning in Deaf Students in TK B at SLB B Pangudi Luhur. This research employs a qualitative case study method involving data collection through interviews and documentation studies. Data analysis is conducted using the Miles and Huberman approach. Data validity is ensured through triangulation from various sources and maintained throughout the research process. The results of this study show that suprasegmental phoneme learning applies two forms of learning activities with different processes and applications in each form of activity, namely found in speech development learning (whose material is obtained from conversations/visualizations that are clarified with curved phrases to familiarize how students can read rhythmically with the Maternal Reflective Method (MRM) in class) and PKPBI. The learning of suprasegmental phonemes set in the TK B class of SLB B Pangudi Luhur is called an ‘accent’ (a sentence spoken with a certain tone/pressure. Some factors influence the learning of suprasegmental phonemes, namely supporting factors, including student focus, student dB, facial direction, oral motor, student motivation, and support from parents. On the other hand, the factors inhibiting the process include students who are sick, a limited amount of time, teachers who have not mastered the material, and a lack of support from the parents.